Lattice mismatch alleviation in p-CdTe/n-Si heterostructure by surface engineering on Si substrate - Isah M.; Doroody C.; Rahman K.S.; Harif M.N.; Kiong T.S.; Zuhdi A.W.M. (Elsevier Ltd, 2024)
The study used magnetron sputtering to investigate the growth of cadmium telluride (CdTe) thin films on surface treated n-type silicon (n-Si) substrates. The n-Si substrates were textured using potassium hydroxide (KOH) before the sputter deposition of CdTe. This was followed by cadmium chloride treatment to reduce the strain at the interface of CdTe and Si, which is caused by the incompatible lattice and thermal expansion mismatch (CTE). X-ray diffraction (XRD) analysis showed that the lowest FWHM and dislocation densities were obtained for CdCl2/CdTe/txt-nSi, which aligns with the scanning electron microscopy (SEM) results. In the SEM images, the interface bonding between the CdTe and Si surfaces was visible in the cross-sections, and the top-view images revealed sputtered CdTe thin films conforming to the patterns of pyramidal textured Si as an engineered surface to capture more light to maximize absorption in the CdTe/Si tandem design. The Energy dispersive X-ray (EDX) results showed that all the CdTe deposited on textured n-Si exhibited more Te atoms than Cd atoms, irrespective of the CdCl2 treatment. The presented results suggest that the texturization and CdCl2 treatment improved the morphology and grain boundary passivation of the sputtered CdTe. The adhesiveness of CdTe on the n-Si substrate was also significantly enhanced. Our findings further demonstrate that proper surface treatment of the Si substrate can greatly improve the quality of CdTe grown on Si by reducing the strain that occurs during the growth process. This study demonstrates a valuable method for enhancing the integration of CdTe with Si for two-junction tandem solar cell applications. 2023 The Authors